A rare entity: Giant pelvic dedifferentiated solitary fibrous tumor: Pelvic solitary fibrous tumor - Aytaç, Adil; Kasapoğlu, Hüseyin; Yanık Keyik, Bahar; Başbuğ, Murat; Turan, Gülay (Journal of Surgery and Medicine, 2024)
Solitary fibrous tumors are a rare soft tissue tumor of mesenchymal origin with variable behavior. The clinical presentation of solitary fibrous tumors is related to the local mass effect, i.e., the size and localization of the lesion. Although they can occur anywhere in the body, they often originate on lined surfaces within a cavity [pleura, peritoneum, dura]. Such tumors occur in only four to six people out of ten million people annually. Since it is such a rare entity, solitary fibrous tumors may not be considered in the differential diagnosis list when it occurs in uncommon localizations. Solitary fibrous tumors are the “great simulator” of soft tissue tumors. The diagnosis is difficult to make and often requires a multidisciplinary approach integrating clinical, radiological, immunohistochemical and genetic factors. Radiological imaging is usually the first step in the detection of these lesions. Computed tomography and magnetic resonance imaging methods allow us to determine the localization of lesions, assess their size and internal structure, as well as their relationship with adjacent anatomical structures and detect distant metastases. The most important treatment method is excisional surgery. Although radiotherapy and chemotherapy are thought to be effective in reducing recurrence, the global efficacy of these treatment methods has not been clearly demonstrated. In addition, randomized prospective studies with large patient populations evaluating the efficacy of other treatment modalities, such as immunotherapy and targeted therapy, are needed. We reported the CT and MRI findings of a 63-year-old patient who presented with complaints of abdominal distension and was diagnosed with pelvic dedifferentiated solitary fibrous tumor.